Predicting recurrence of non-muscle-invasive bladder cancer after transurethral resection - Haris Đug; Samed Jagodić; Jasmina Ahmetović-Ðug; Zijad Selimović; Alemdar Sulejmanović (Medicinski glasnik, 2016)
Aim: To determine clinical prognostic factors and their impact on the risk of recurrence of newly discovered non-muscle-invasive bladder cancer. Methods: The study included 120 patients of both sexes aged 45-80 years with newly discovered non-muscle-invasive bladder cancer. All the patients were treated surgically by transurethral electro resection (TUER). The outcome of patients with and without recurrence was followed at intervals of three months after surgery, the total of two years. For monitoring the probability of early recurrence the criteria of the European Organization for Research and Treatment of Cancer (EORTC) were used. Results: The average age of the patients was 65.9 years, 79 (79.2%) males and 21 (20.8%) females. The total of 67 (55.8%) patients had a recurrence during the period of monitoring. The average time to the first and fourth recurrence was 15.4 and 23.9 months, respectively. Numbers of tumors and a degree of invasion had a significant prognostic impact on the risk of recurrence. The EORTC score was a highly significant predictor of recurrence (OR=1.237; p<0.001). Conclusion: Based on available clinical and pathological prognostic factors and by stratification of patients into three disease risk groups it is possible to predict the possibility of disease. Individual approach and recommendations for the treatment using EORTC risk tables should improve the quality of treatment.
Keywords: immunotherapy; probability; treatment